2020
DOI: 10.1111/echo.14886
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking echocardiography can predict subclinical myocardial involvement in patients with sarcoidosis: A meta‐analysis

Abstract: Background: This meta-analysis aims to evaluate the utility of speckle tracking echocardiography (STE) as a tool to evaluate for cardiac sarcoidosis (CS) early in its course. Electrocardiography and echocardiography have limited sensitivity in this role, while advanced imaging modalities such as cardiac magnetic resonance (CMR) and 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) are limited by cost and availability. Methods: We compiled English language articles that reported left ventricular glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
(132 reference statements)
0
15
0
Order By: Relevance
“…The sarcoidosis status was classified as worsened if a therapeutic step-up (increase in or start of steroids and/or immunosuppressive drugs) was needed according to the advice of the respiratory physician and/or if evidence of organ damage due to sarcoidosis was identified through a clinical, radiological and laboratory assessment during the follow-up according the latest guidelines [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sarcoidosis status was classified as worsened if a therapeutic step-up (increase in or start of steroids and/or immunosuppressive drugs) was needed according to the advice of the respiratory physician and/or if evidence of organ damage due to sarcoidosis was identified through a clinical, radiological and laboratory assessment during the follow-up according the latest guidelines [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, as a comprehensive guideline, the ATS document focused on “traditional” TTE and, in particular, with the left ventricular (LV) ejection fraction (EF) estimation and wall motion abnormalities related to coronary artery diseases. In the last decade, a new imaging semi-automatic technique of speckle tracking echocardiography (STE) has proven to be more sensitive in the early detection of myocardial damage and less operator-sensitive than traditional TTE [ 13 ]. Not surprisingly, many studies have demonstrated that STE is significantly better than TTE in the early detection of myocardial damage or sarcoid involvement and also in predicting cardiac events in the follow-up of sarcoidosis patients [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a meta-analysis performed by Barssoum K. et al, comprising 9 studies and 967 subjects, proved that both LV GLS and global circumferential strain are substantially lower in extracardiac sarcoidosis subjects and no clinical evidence of cardiac involvement and that the degree of LV GLS impairment correlates with the occurrence of major cardiac events [62]. Additionally, the circumferential strain has proved to be an indicator of fibrosis burden in subjects with extracardiac sarcoidosis.…”
Section: Advanced Echocardiographic Techniques In Sarcoidosismentioning
confidence: 99%
“…Additionally, multiple observational studies have demonstrated that reductions in GLS may be identified by STE in patients with sarcoidosis without known CS or apparent LV dysfunction, suggestive of early subclinical myocardial dysfunction (24)(25)(26)(27). A recent meta-analysis of these studies found that LVGLS was significantly impaired in patients with extracardiac sarcoidosis and normal LV function compared with controls, and that among patients with sarcoidosis, LVGLS was significantly reduced in patients who experienced major cardiac events (28). These studies suggest a potential role for STE as a more sensitive screening tool than traditional echocardiography alone to identify patients with extracardiac sarcoidosis at increased risk for cardiac involvement.…”
Section: Echocardiographymentioning
confidence: 99%